The impact of spectrum policy on carbon emissions - Jakub Zagdanski; Pau Castells (International Telecommunications Society (ITS), 2023)
By assigning rights and conditions of use, spectrum policy regulates how radio frequencies can be used by mobile networks. We develop a parameterised calculator tool to estimate the impact of various spectrum policy aspects on the emissions of the mobile sector. We model the impacts during the main phase of 5G rollout (2022-2031) in representative medium-sized low-income and high-income countries. (population: 80 million). We find that the carbon footprint of the mobile sector can increase between 1% (up to 0.4 MtCO2e) as a result of fragmented 5G spectrum, and up to 9% ( up to 2.6 MtCO2e) as a result of a two year-delay to 5G assignment Importantly, we find that the potential impact on the emissions of other sectors and households as a result of lower adoption of emission-saving use cases could be many times greater. A two-year delay to assignment of 5G spectrum could lead to emissions in other sectors and households increasing by up to 37 MtCO2e.
Keywords: Q54; Q58; D44; 330; Radio spectrum; spectrum policy; emissions; climate change